Refuge and Asylum of Bolivians During the Chilean Dictatorship. 1973 and 1975 [Refugio y Asilo de Bolivianos Durante la Dictadura Chilena Entre 1973 y 1975 - Norambuena-Carrasco, C; Palomera-Valenzuela, A (Universidad de Tarapaca, 2018)
Our hypothesis is that Chile in the 1970 s presented two different scenarios. At first, it appeared as a reliable country, where one could migrate, go into exile or seek refuge, trusting that the socialist government could receive anyone who felt threatened in their home countries. After the 1973 military coup, the country s socio-political conditions varied, whereupon people began to move out seeking political asylum or directly into exile. Under such circumstances, it is necessary to delve into the conceptual difference between one situation and another. This article deals specifically with the experience of political refuge and asylum of Bolivian nationals in Chile during the presidency of Salvador Allende and the early years of military dictatorship. Because refugee protection became a continent-wide problem, the involvement of international agencies such as the United Nations High Commissioner for Refugees, the Inter-Governmental Committee for European Migrations, the National Committee for Refugee Aid and the United Nations, became mandatory. The methodology applied is fundamentally based on documentary evidence, such as safe-conducts issued by Chile s Ministry of Foreign Relations, which demonstrate a process that in this paper is defined as a "double refuge". © 2018, Universidad de Tarapaca.; Partimos de la hipótesis de que Chile en la década de los años setenta tuvo dos escenarios diferentes. En los inicios se configuró como un país confiable al que se podría emigrar, exiliarse o solicitar refugio con la certeza de que, debido a las características del régimen socialista, este podía albergar a todos aquellos que se sintieran amenazados en sus países de origen. Luego del golpe militar de 1973, el panorama político-social del país cambió. Bajo estas condiciones, se produjeron movimientos de personas asociadas a situaciones de asilo, exilio y refugio, razón por la que es preciso discurrir acerca de su diferencia conceptual. Este artículo trata específicamente del refugio y asilo de bolivianos en Chile entre el gobierno del presidente Salvador Allende y los inicios de la dictadura militar. A causa de que la protección de refugiados se convirtió en una problemática regional, demandó la intervención de organismos internacionales como el Alto Comisionado de las Naciones Unidas para los Refugiados (ACNUR); el Comité Intergubernamental para las Migraciones Europeas (CIME), el Comité Nacional para Ayuda a los Refugiados (CONAR), y la Organización de las Naciones Unidas (ONU). La metodología utilizada se basa fundamentalmente en el análisis de información documental, como los salvoconductos emitidos por el Ministerio de Relaciones Exteriores de Chile, que permiten evidenciar un proceso que, en este escrito, denominaremos "doble refugio". © 2018, Universidad de Tarapaca.